2023
DOI: 10.1097/ede.0000000000001589
|View full text |Cite
|
Sign up to set email alerts
|

Douching and Genital Talc Use: Patterns of Use and Reliability of Self-reported Exposure

Abstract: Background: Feminine hygiene products contain chemicals that may be harmful to human health. Observational studies of the longterm health effects of such products largely rely on self-reported, recalled exposure. We sought to capture patterns of use over the life course and evaluate the reliability of self-reported data. Methods: We collected retrospective data on douching and genital talc use in the US-based Sister Study at two-time points and evaluated the consistency of reporting. At enrollment (2003)(2004)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Scenario 2 assumes 99% sensitivity and specificity for cases' recall, and 82% sensitivity and 99% specificity for controls' recall, which is the amount of misclassification reported by the authors that would nullify the risk estimate. For Scenarios 3 and 4, we used the sensitivity and specificity reported in O'Brien et al [ 13 ] for cases (83 and 87%, respectively, and their respective 95% CIs which were calculated using the EpiR [ 16 ] package in R v4.3.1 [ 17 ]), with 0–5% exposure misreporting among controls in Scenario 3, and 63% sensitivity and 95% specificity and their respective 95% CIs for controls in Scenario 4 (as reported for the whole cohort by O'Brien et al [ 13 ]). For Scenarios 5–7, we assumed the sensitivities and specificities ranged between 90 and 100%, to reflect the potential for lower levels of recall bias that have been reported for other self-reported exposures [ [9] , [10] , [11] , [12] ].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Scenario 2 assumes 99% sensitivity and specificity for cases' recall, and 82% sensitivity and 99% specificity for controls' recall, which is the amount of misclassification reported by the authors that would nullify the risk estimate. For Scenarios 3 and 4, we used the sensitivity and specificity reported in O'Brien et al [ 13 ] for cases (83 and 87%, respectively, and their respective 95% CIs which were calculated using the EpiR [ 16 ] package in R v4.3.1 [ 17 ]), with 0–5% exposure misreporting among controls in Scenario 3, and 63% sensitivity and 95% specificity and their respective 95% CIs for controls in Scenario 4 (as reported for the whole cohort by O'Brien et al [ 13 ]). For Scenarios 5–7, we assumed the sensitivities and specificities ranged between 90 and 100%, to reflect the potential for lower levels of recall bias that have been reported for other self-reported exposures [ [9] , [10] , [11] , [12] ].…”
Section: Methodsmentioning
confidence: 99%
“…Recall error rates have been reported in several studies that used self-reported exposures ( e.g. , [ [9] , [10] , [11] , [12] ]), but to the best of our knowledge, only one such study has examined recall of perineal talc use [ 13 ]. O'Brien et al [ 13 ] evaluated data from the Sister Study, a US-based prospective cohort study of women aged 35–74 who had a sister with a history of breast cancer.…”
mentioning
confidence: 99%
See 3 more Smart Citations